Homogenization of the Signorini boundary-value problem in a thick plane junction - Kazmerchuk, Yu.A.; Mel’nyk, T.A. (Нелінійні коливання, 2009)
We consider a mixed boundary-value problem for the Poisson equation in a plane thick junction Ωε which is the union of a domain Ω₀ and a large number of ε-periodically situated thin rods. The nonuniform Signorini conditions are given on the vertical sides of the thin rods. The asymptotic analysis of this problem is made as ε → 0, i.e., when the number of the thin rods infinitely increases and their thickness tends to zero. With the help of the integral identity method we prove the convergence theorem and show that the nonuniform Signorini conditions are transformed (as ε → 0) in the limiting variational inequalities in the region that is filled up with the thin rods when passing to the limit. Existence and uniqueness of the solution to this non-standard limit problem is established. The convergence of the energy integrals is proved as well.